Anti-hyperalgesic effect of Mangifera indica L. extract on the sciatic chronic constriction injury model in rats - Bárbara B. Garrido-Suárez; Marian Castro Labrada; Nelson Merino; Odalys Valdés; René Delgado-Hernández (GarVal Editorial Ltda., 2014)
Context: The aqueous extract of Mangifera indica L. stem bark (MSBE) shows antioxidant, anti-inflammatory and analgesic properties. Aims: To test the MSBE in chronic constriction injury (CCI) of the sciatic nerve in rats, a classical model of neuropathic pain. Methods: Given the possibility that some clinical effect of MSBE can appear only after its chronic administration, we designed a long term medication protocol with 500 mg/kg, p.o. or distilled water daily during 8 days from 9 days post-CCI. Pregabalin (10 mg/kg, p.o.) was used as reference drug. Sham CCI animals received vehicle. Behavioral tests were carried out before CCI, at 9 and 16 days after injury. A section of sciatic nerve, 5 mm distal to the ligature site was dissected for histopathological studies. A single oral similar dose or vehicle was administered to mononeuropathic rats, 14 days after surgery. Mechano-hyperalgesia and thermal hyperalgesia of the ipsilateral paw were determined using a modification of pin prick method and the unilateral hot plate, respectively before CCI, 0, 30, 60, 120 and 180 min post-administration. Results: Repeated oral MSBE doses reduced nociceptive score, increased paw withdrawal latency and attenuated CCI-induced Wallerian degeneration-related changes involved in the hyperalgesic state of CCI rats. Likewise, MSBE shows significant mechanical and thermal anti-hyperalgesic effect from 1h after its single administration. Conclusions: The study of MSBE should be focused in neuropathic pain models since this natural product could have a clinical relevance in the treatment of neuropathic pain syndromes.